Sperm cryopreservation protocol for micro-TESE-retrieved sperm - Vijay Mangoli; Evangelini Evgeni; Christine Wyns (Asian Journal of Andrology)
Azoospermia is characterized by the absence of sperm in the ejaculate and is categorized into obstructive azoospermia (OA) and nonobstructive azoospermia (NOA). For men with NOA, testicular sperm extraction (TESE) is the only method to obtain sperm for assisted reproductive technology (ART). Given the rarity of these sperm and the unpredictable success of subsequent retrieval attempts, cryopreservation of microdissection-TESE-obtained sperm is essential. Effective cryopreservation prevents the need for repeated surgical procedures and supports future ART attempts. After first delving into the physiological and molecular aspects of sperm cryopreservation, this review aims to examine the current methods and devices for preserving small numbers of sperm. It presents conventional freezing and vitrification techniques, evaluating their respective strengths and limitations in effectively preserving rare sperm, and compares the efficacy of using fresh versus cryopreserved testicular sperm.